Computation of Surge Voltage in Transmission Tower Located above Frequency-Dependent Soil - Justo De Araujo, Anderson Ricardo; Manzi De Azevedo, Walter Luiz; Filho, Jose Pissolato; Leon Colqui, Jaimis Saiid; Kurokawa, Sergio; Kordi, Behzad (Institute of Electrical and Electronics Engineers (IEEE), 2021)
The purpose of this paper is to investigate the influence of frequency-dependent soils with variable soil content on the transient voltages at transmission towers. First, a comparative analysis between the impedance of tower-footing grounding rods buried in frequency-independent and frequency-dependent soils is carried. Then, the performance of ground potential rise (GPR) subjected to two types of lightning currents (first and subsequent return strokes) is studied. In a second part, these grounding rods are connected into a single-circuit transmission tower where the admittance of the structure located on frequency-independent and frequency-dependent soil is computed. The surge voltages generated by the two lightning currents are studied for these two types of soil. The frequency-domain responses are computed using the numerical method of Moments based on Electric Field Integral Equations in a frequency range from 100 Hz up to 10 MHz. Numerical results demonstrate that the frequency dependency of soil electrical parameters results in a modification of the rod impedance, especially at high frequencies. As a consequence, when the frequency-dependent soil is considered, a reduction at the transient voltage peaks is obtained compared with those calculated for a frequency-independent soil. This reduction is more pronounced when the transmission tower is located on the soil of high resistivity and subjected to a subsequent return stroke due to its higher energy at the high frequencies.
Keywords: Electromagnetic transients; Ground potential rise; Grounding grid; Water content